Measuring Weathering and Nanoparticle Coating Impact on Surface Roughness of Natural Stones. (4th July 2019) - Raneri, Simona; Crezzini, Jacopo; Arrighi, Simona; Boschin, Francesco; Alfieri, Ilaria; Barone, Germana; Bergamonti, Laura; Giamello, Marco; Lottici, Pier Paolo; Mazzoleni, Paolo
ABSTRACT: The surface texture of a stone represents a sensitive parameter in evaluating its conservation state. In monuments and sculptures, in fact, external agents continuously alter the appearance of stones, determining peculiar weathering patterns and modifying properties such as retention of water and particles, interaction with light, color, and finishing. The application of protective coatings also determines changes in surface appearance of a stone, usually evaluated and monitored by color change tests. Surface metrology methods offer the possibility to quantify these changes, evaluating the impact of external agents (natural, i.e. weathering, and artificially, i.e. protective coatings) on natural stones. In this research, we demonstrate the potential of surface areal measurements in describing the evolution of weathering processes and the effects of protective treatments on porous stone materials. The obtained results suggest that the extent of the modifications is related to the scale of observation (small- vs. large-scale undulations, i.e. roughness and waviness, respectively), with an overall increase of surface roughness as the weathering proceeds. Unexpectedly, coatings based on nanoparticle dispersions increase the topographic height parameters, due to the absence of a homogeneous film.